2008
DOI: 10.3181/0710-mr-267
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia: Cause of or Therapy for Systemic Hypertension?

Abstract: During acute episodes of hypoxia, chemoreceptor-mediated sympathetic activity increases heart rate, cardiac output, peripheral resistance and systemic arterial pressure. However, different intermittent hypoxia paradigms produce remarkably divergent effects on systemic arterial pressure in the post-hypoxic steady state. The hypertensive effects of obstructive sleep apnea (OSA) vs. the depressor effects of therapeutic hypoxia exemplify this divergence. OSA, a condition afflicting 15-25% of American men and 5-10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
129
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 207 publications
(234 reference statements)
4
129
0
5
Order By: Relevance
“…At the same time, it has been demonstrated that IHT may normalize blood pressure in hypertensive patients [123,124]. Moreover, it has been shown that systolic blood pressure is reduced after IHT, causing a hypotensive effect [43].…”
Section: Intermittent Hypoxic Training (Iht)mentioning
confidence: 99%
“…At the same time, it has been demonstrated that IHT may normalize blood pressure in hypertensive patients [123,124]. Moreover, it has been shown that systolic blood pressure is reduced after IHT, causing a hypotensive effect [43].…”
Section: Intermittent Hypoxic Training (Iht)mentioning
confidence: 99%
“…Repeated episodes of hypobaric hypoxia interspersed with normoxic periods [intermittent hypobaric hypoxia (IH)] have long been used for training pilots, mountaineers, and athletes, and even applied for treatment and prevention of human diseases such as hypertension (Serebrovskaya et al, 2008), ischemic coronary artery diseases (Zhu et al, 2006), Parkinson's disease (Lin et al, 2002), and acute myeloid leukemia (Liu et al, 2006). Recently, it has been shown that hypoxia promoted neurogenesis in vitro (Shingo et al, 2001;Jin et al, 2002) and enhanced the proliferation of neuroprogenitor cells (NPCs) in vivo (Zhu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies reveal that augmented activity of the CB, induced by IH plays an important role in the pathogenesis of sleep apnea [13] in anesthetized rats and humans and emphasis is being made to understand its underlying mechanisms. Furthermore, the equilibrium between HIF1α and HIF2α, hampered by chronic IH leads to an imbalance between pro-oxidant and antioxidant enzymes respectively that causes oxidative stress resulting in pathophysiology [14][15][16] and has been implicated as a risk factor for an array of cardiovascular diseases [17] affecting humans.…”
Section: Introductionmentioning
confidence: 99%